2014
DOI: 10.11604/pamj.2014.19.332.5159
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance: capacity and practices among clinical laboratories in Kenya, 2013

Abstract: IntroductionAntimicrobial resistance is neglected in developing countries; associated with limited surveillance and unregulated use of antimicrobials. Consequently, delayed patient recoveries, deaths and further antimicrobial resistance occur. Recent gastroenteritis outbreak at a children's home associated with multidrug resistant non-typhoidal Salmonella spp, raised concerns about the magnitude of the problem in Kenya, prompting antimicrobial resistance assessment preceding surveillance system establishment.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Most hospitals in Kenya lack the capacity to carry out antimicrobial sensitivity tests, due to the lack of resources and technical knowhow, among other challenges. 31 This study will first provide an assessment to determine the challenges hospitals are facing; this will be done through interviews with clinicians and assessment of the capacity of the laboratories to perform the sensitivity tests. These steps will make up the initial phase and will guide the nature of implementations to be used during the implementation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Most hospitals in Kenya lack the capacity to carry out antimicrobial sensitivity tests, due to the lack of resources and technical knowhow, among other challenges. 31 This study will first provide an assessment to determine the challenges hospitals are facing; this will be done through interviews with clinicians and assessment of the capacity of the laboratories to perform the sensitivity tests. These steps will make up the initial phase and will guide the nature of implementations to be used during the implementation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone-resistant invasive NTS infections rapidly emerged during 2009-2014 in this area of western Kenya, where malaria and HIV are endemic (Fig 1). The true prevalence of multidrug-resistant NTS infections may be even larger than the prevalence these research and surveillance programs identified, because many infections are undetected due to lack of microbiologic diagnostic capacity in standard clinical settings and the absence of surveillance systems that track antimicrobial resistance in Kenya [15].…”
Section: Discussionmentioning
confidence: 99%
“…The practice of dispensing antimicrobials for veterinary use was similar to that for human use; antibiotic purchase without a prescription, treatment without veterinarian's consult and subtherapeutic dosing were common. Agrovets also sold a wide range of antimicrobials for animal use to which ceftriaxone-resistant NTS in humans were co-resistant; all or most of the 15 interviewed agrovets sold sulfonamides (15), beta-lactams (14), tetracyclines (13) and macrolides (13) (S3 Table). In addition to antimicrobials, more than half of commonly sold brands of poultry nutritional supplements had tetracycline or oxytetracycline additives (15 of 27 observed supplements) that could contribute to co-selection of ceftriaxone-resistance.…”
Section: Survey Findings Regarding Antimicrobial Availability and Usementioning
confidence: 99%
“…Similar resistance pattern for Ampicillin (100%) was also observed in a study conducted in Kenya. 20 A study in Ethiopia also documented to Amikacin and Ciprofloxacin, ((66.7%), each). Similar resistance pattern for Ampicillin (100%) was also observed in a study conducted in Kenya.…”
mentioning
confidence: 96%
“…Similar resistance pattern for Ampicillin (100%) was also observed in a study conducted in Kenya. 20 This similarity of the increase in the pattern of the antimicrobial resistance in the low income Eastern African countries and Eritrea could be attributed to similar climate change, societal belief and culture, access to antimicrobial drugs and achievement to modern medicine.…”
mentioning
confidence: 97%